2017
DOI: 10.1001/jamapsychiatry.2017.2145
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Purpose in Life and Objective Measures of Physical Function in Older Adults

Abstract: Purpose in life was prospectively associated with a decreased risk of developing weak grip strength and slow walking speed, although the findings were more robust for walking speed than for grip strength. These findings suggest that a sense of purpose in life, a modifiable factor, may play an important role in maintaining physical function among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 67 publications
1
65
1
6
Order By: Relevance
“…A further recent population-scale study has demonstrated that strong handgrip strength is also positively related to purpose in life, which could also contribute toward explaining the relationships shown here. 38 Another possible explanation to our findings is the proinflammatory state of participants who experience sarcopenia (loss of muscle mass and muscle strength) 39 may operate the pathway to suicidal thought. Mechanistic studies on suicide have been largely focused on psychosocial factors.…”
Section: Discussionmentioning
confidence: 86%
“…A further recent population-scale study has demonstrated that strong handgrip strength is also positively related to purpose in life, which could also contribute toward explaining the relationships shown here. 38 Another possible explanation to our findings is the proinflammatory state of participants who experience sarcopenia (loss of muscle mass and muscle strength) 39 may operate the pathway to suicidal thought. Mechanistic studies on suicide have been largely focused on psychosocial factors.…”
Section: Discussionmentioning
confidence: 86%
“…13,16 Recently, PWB levels were found to be associated with a decreased genetic response in activating a proinflammatory reaction when facing stress. 25,26 Thus, it seems that PWB entails biological underpinnings that may buffer in case of distress or disease, 27 moderating the onset of psychological and physical illnesses. 25,26 Thus, it seems that PWB entails biological underpinnings that may buffer in case of distress or disease, 27 moderating the onset of psychological and physical illnesses.…”
mentioning
confidence: 99%
“…24 Recent investigations documented that the dimension of purpose in life is particularly important in moderating the effect of chronic illnesses, cognitive deterioration and even mortality. 13,14,16,[25][26][27][28][29][30][31] Although subjective and eudaimonic well-being are differentiated by empirical and conceptual points of view, their combination defines flourishing or optimal mental health 32,33 and they are both considered key ingredients of positive aging. 13,14,16,[25][26][27][28][29][30][31] Although subjective and eudaimonic well-being are differentiated by empirical and conceptual points of view, their combination defines flourishing or optimal mental health 32,33 and they are both considered key ingredients of positive aging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted the impact that psychological factors, “such as having a purpose in life,” have on living longer lives (Cohen, Bavishi, & Rozanski, 2016), in addition to maintaining physical functioning (Kim, Kawachi, Chen, & Kubzansky, 2017). Wong et al (2014) also reported four themes related to living long and well: positive relations with others, positive events and happiness, hope for the future, and positive life attitude.…”
Section: Introductionmentioning
confidence: 99%